Rawls and Selective Justice in Nigeria: A Philosophical Examination (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This paper applies John Rawls’ Theory of Justice to interrogate the persistent problem of selective justice in Nigeria, drawing on three recent incidents as revealing case studies. The first involves Adams Oshiomhole, who confronted airline staff, occupied the terminal entrance, and disrupted operations yet faced no formal punitive outcome. The second concerns Fuji music icon Wasiu Ayinde Adewale (Kwam 1), who obstructed an aircraft in a grave aviation safety breach but was initially subjected only to a six-month travel ban, later quietly lifted. The third case is that of Ms. Comfort Emmanson, who was handed a lifetime flight ban for alleged unruly behaviour – a sanction that was immediate, uncompromising, and absolute. While all three incidents involve breaches of legal or ethical norms, the starkly divergent institutional and legal responses reveal a justice system that consistently tilts in favour of the influential while applying swift and severe punishment to the less powerful. The paper asks: to what extent does Nigeria’s justice system align with Rawls’ conception of justice as fairness? How do privilege, social status, and political influence shape the uneven enforcement of justice? Analysed through the lens of Rawls’ principles—particularly the veil of ignorance, the guarantee of equal basic rights, and the difference principle—these cases demonstrate a troubling departure from the ideal of “justice as fairness.” Instead, Nigeria’s current enforcement patterns evoke the ancient observation that laws ensnare the weak while allowing the strong to break free. By critically examining these disparities, the study seeks to illuminate pathways toward a more equitable and principled system of justice.